Crystallization of the NADP(+)-dependent glutamate dehydrogenase from Escherichia coli. - Korber, F; Rizkallah, P; Attwood, T; Wootton, J; McPherson, M; North, A; Geddes, A; Abeysinghe, I; Baker, P; Dean, J (1993)
The NADP(+)-dependent hexameric glutamate dehydrogenase from Escherichia coli has been crystallized as the apo-enzyme and also in the presence of its substrates 2-oxoglutarate, glutamate or NADP+, using either pulsed equilibrium microdialysis, or the hanging drop method of vapour diffusion. Three non-isomorphous, but related, crystal forms have been obtained, all of which belong to the orthorhombic system and are most likely to be in space group P2(1)2(1)2(1). One crystal form is grown from ammonium sulphate, includes the apoenzyme and the binary complexes with 2-oxoglutarate or NADP+, and has cell dimensions a = 157.5 A, b = 212.5 A, c = 101.0 A with a hexamer in the asymmetric unit. Crystallizations using glutamate as the precipitant produced two further crystal forms, which show significant changes in the b and c cell dimensions with respect to the apo-enzyme crystals, with parameters a = 160.0 A, b = 217.5 A c = 92.4 A and a = 160.0 A, b = 223.0 A c = 92.4 A, respectively. X-ray diffraction photographs taken with synchrotron radiation show measurable reflections to beyond 3.0 A resolution.